An Ecofeminism Analysis of Axie Oh’s Novel “The Girl Who Fell Beneath the Sea” - Mega Lestari; Hana Farida (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study pursues the analysis of chosen work novel by Axie Oh novel The Girl Who Fell Beneath The Sea through the lens of ecofeminism. The crux of ecofeminsim is the relationship between nature and women. The research applies descriptive qualitative method the novel serves as the primary data and the secondary data are works similar to the theory of ecofeminism. Data were collected through library technique, including close reading and textual selection, and analyzed through Moleong in the form of words, sentences, dialogues, and thematic interpretation. This research serve a fresh perspective on sacrifice, agency, and ecological symbolism, offering new insights into how modern narratives articulate the relationship between women, patriarchy, and the environment. As the results it finds that the novel reflect women and nature are deeply interconnected from an ecofeminism perspective. Through three main aspects, the novel illustrates this connection through themes of women’s interaction with nature, patriarchal dominance, and the exploitation of women, which together highlight how human proximity to nature is represented.